The Projection of Iran's Healthcare Expenditures By 2030: Evidence of a Time-Series Analysis - Nader Jahanmehr; Mohammad Noferesti; Soheila Damiri; zhaleh Abdi; Reza Goudarzi (Kerman University of Medical Sciences, 2022)
Background  The projection of levels and composition of financial resources for the healthcare expenditure (HCE) and relevant trends can provide a basis for future health financing reforms. This study aimed to project Iran's HCEs by the sources of funds until 2030.Methods  The structural macro-econometric modeling in the EViews 9 software was employed to simulate and project Iran's HCE by the sources of funds (government health expenditure [GHCE], social security organization health expenditure [SOHCE], out-of-pocket [OOP] payments, and prepaid private health expenditure [PPHCE]). The behavioral equations were estimated by autoregressive distributed lag (ARDL) approach.Results  If there is a 5%-increase in Iran's oil revenues, the mean growth rate of gross domestic product (GDP) is about 2% until 2030. By this scenario, the total HCE (THCE), GHCE, SOHCE, OOP, and PPHCE increases about 30.5%, 25.9%, 34.4%, 31.2%, and 33.9%, respectively. Therefore, the THCE as a percentage of the GDP will increase from 9.6% in 2016 to 10.7% in 2030. It is predicted that Iran's THCE will cover 22.2%, 23.3%, 40%, and 14.5% by the government, social security organization (SSO), households OOP, and other private sources, respectively, in 2030.Conclusion  Until 2030, Iran's health expenditures will grow faster than the GDP, government revenues, and non-health spending. Despite the increase in GHCE and total government expenditure, the share of the GHCE from THCE has a decreasing trend. OOP payments remain among the major sources of financing for Iran's HCE.